A hybrid PSO-GWO-based phase shift design for a hybrid-RIS-aided heterogeneous network system - Abdel Nasser Soumana Hamadou; Ciira wa Maina; Moussa Moindze Soidridine (Heliyon, 2024)
The effectiveness of developing reconfigurable intelligent surfaces (RIS) for heterogeneous network (HetNet) systems has resulted in significant spectral efficiency (SE) gains. The majority of current research has not addressed effectively whether a hybrid metaheuristic technique may be used to create the hybrid RIS phase changes in HetNet. In this paper, we study a heterogeneous network (HetNet) assisted by a hybrid reconfigurable intelligent surface (H-RIS). Compared with the passive RIS, a hybrid RIS that has only 8% active elements is proposed to enhance by reflecting and amplifying incident signals. Hybrid RIS phase shift and SBS transmit beamforming are optimised. At the SBS, transmit beamforming based on zero-forcing is employed, whereas for hybrid RIS phase shift optimisation, the hybrid PSO-GWO (HPSOGWO) method is employed. The exploitation power of particle swarm optimisation (PSO) and the exploration power of the grey wolf optimizer (GWO) are combined in this hybrid approach. Simulation findings show that the suggested method, which uses only modest active RIS elements, can achieve a significant spectral efficiency improvement over both RIS-aided HetNet with totally passive RIS elements but with the SDR method to optimise the RIS phase changes and RIS-aided HetNet with entirely active RIS elements but with the Lagrange multiplier (LM) scheme to design the phase shift at the active RIS.